Estimation of Liquefaction with UBC3D-PLM Model: A Centrifuge Test Example - Demir, Selcuk; Ozener, Pelin (TURKISH CHAMBER CIVIL ENGINEERS, 2019)
In this study, a centrifuge test presented in the literature is numerically modeled with UBC3D-PLM model and obtained results are compared experimentally and numerically to predict liquefaction behavior. First, the material parameters and calibration steps required for the UBC3D-PLM model are mentioned and the behavior of the soils used in the centrifuge model test under monotonic and cyclic loads is calibrated to represent a similar behavior in the numerical model. By using the material parameters obtained from the calibration, the centrifuge experiment is numerically modelled. As a result of the numerical analysis, the computed excess pore water pressure, acceleration and displacements are compared with the values measured in the experimental study and consistent results are obtained in terms of onset of liquefaction, excess pore water pressure development, and time history of accelerations. However, similar responses are not obtained from excess pore pressure dissipation and displacement results.
Keywords: UBC3D-PLM; UBCSAND; liquefaction; numerical analysis; SEISMIC LIQUEFACTION; Engineering